Islam early architecture from Baghdad to Cordoba - Stierlin, Henri; Stierlin, Anne. (New York Taschen, 1996)
"This volume is an impressive survey of more than 600 years of Islamic architecture, from the seventh to the thirteenth centuries, in a region stretching from the Near and Middle East to Sicily, the Maghreb and Andalusia. It presents masterpieces of Islamic architecture from the peerless Dome of the Rock in Jerusalem to the mysterious Umayyad palaces in the deserts of Syria and Palestine, from the sumptuous residences of the caliphs in Samarra and Saragossa to the Great Mosques of Damascus, Kairouan and Cordoba."--Provided by publisher.
Translated from German.
Includes bibliographical references and indexes.
Keywords: Islamic architecture; Architecture, Medieval